1998
DOI: 10.1001/archotol.124.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Basic Fibroblast Growth Factor on Irradiated Porcine Skin Flaps

Abstract: This study provides evidence that supplemental bFGF can increase vascularity to skin flaps in previously irradiated porcine skin tissue. Histologically, radiation did not prevent the angiogenic effect of bFGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…33 Chang et al, 22 using a porcine model, found a 62% increase in vascularity in irradiated flaps treated with bFGF. Previous studies that used irradiated animal models in conjunction with FGFs have shown mixed results in irradiated conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…33 Chang et al, 22 using a porcine model, found a 62% increase in vascularity in irradiated flaps treated with bFGF. Previous studies that used irradiated animal models in conjunction with FGFs have shown mixed results in irradiated conditions.…”
Section: Discussionmentioning
confidence: 98%
“…22 Treated and control flaps were then harvested from the side of the pig by means of the previous incision lines. On postoperative day 14, after completion of tissue oximetry measurements, each animal was sedated by means of the regimen described previously, and porcine heparin (1 mg/kg) was administered by intravenous injection.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically this can have a signi cant impact, since the induction and inhibition of angiogenesis have an implementation in many diseases [43][44][45][46][47]. The therapeutic angiogenic process can be in uenced by direct stimulation with angiogenic growth factors or via growth factors that are known to stimulate the release of angiogenic factors from cells.…”
Section: Original Researchmentioning
confidence: 99%
“…Thus, supplemental bFGF may be important for irradiated postsurgical soft tissue healing. It has been shown that the use of bFGF prior to bone grafting improved vascularity in the irradiated soft tissue bed, which reduced the risk of bone graft failure [29], and that intravenous bFGF improved random skin flap viability and increased skin flap tolerance to irradiation [27,30].…”
Section: Evaluation Of the Hypothesis/ideamentioning
confidence: 99%